2019
DOI: 10.25139/dinamika.v5i1.1606
|View full text |Cite
|
Sign up to set email alerts
|

Swear Words Used by John Benett in Ted 2 Movie Script

Abstract: The thesis writer focuses on the analysis swear words used by John Bennett in Ted 2 movie script. The objectives of the study are, to find out the types of swear word used by john Bennett in Ted 2I movie script, and  the reasons of John Bennett using swear words in Ted 2 movie script. The thesis writer applies the theory Liedlich (1973) to find the types of Swearing and applies the theory of Neel Burton (2012) to find The Reasons of Swearing and the thesis writer also applies a qualitative research.Key Word: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…People who only imitate English swearwords do not understand the literal meanings of the swearwords they utter. Swearwords can be polite when they elevate social harmony, but they can be rude when they are used to assault others (Sarmi & Putra, 2017). English swear words are recognized all around the world, and used in movies, literature, and TV shows, and affirms that swear words are one of the types of English words most people learn before they properly learn English (Jumanto and Sulistyorini, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…People who only imitate English swearwords do not understand the literal meanings of the swearwords they utter. Swearwords can be polite when they elevate social harmony, but they can be rude when they are used to assault others (Sarmi & Putra, 2017). English swear words are recognized all around the world, and used in movies, literature, and TV shows, and affirms that swear words are one of the types of English words most people learn before they properly learn English (Jumanto and Sulistyorini, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, informal swear words relates to bad language, foul language, or emotional expression. (Crystal, 2003) also thinks in (Sari, 2021) that swear words are like an explosion, an explosion that brings relief to an angry or emotional person, so that it becomes a substitute for the body's response shown to people or something. Another explanation from (Crystal, 2003)as cited in (Rahmawati, 2013) stated that swear words are used to express emotions or expressions of someone who is angry because at that time people need harsh words that are inappropriate to say to show their anger.…”
Section: Definition Of Swear Wordsmentioning
confidence: 99%
“…Many empirical studies also found to expose about English swearing words in movie (Sanusi, 2014;Sarmi, 2017;Khoirunnisa, 2017;Puspitasari, 2017;Prayuda, Suarnajaya & Juniarta, 2019;Rinaldi, 2020;Salim & Setiawan, 2020;. All those researchers concerned to the use and types of English swearing in a certain movie.…”
Section: Introductionmentioning
confidence: 99%